High plasmodium malariae prevalence in an endemic area of the colombian amazon region (2016)
Malaria is a worldwide public health problem; parasites from the genus Plasmodium are the aetiological agent for this disease. The parasites are mostly diagnosed by conventional microscopy-based techniques; however, their limitations have led to under-registering the reported prevalence of Plasmodium species. This study has thus been aimed at evaluating the infection and coinfection prevalence of 3 species of Plasmodium spp., in an area of the Colombian Amazon region. Blood samples were taken from 671 symptomatic patients by skin puncture; a nested PCR amplifying the 18S ssRNA region was used on all samples to determine the presence of P. vivax, P. malariae and P. falciparum. Statistical analysis determined infection and coinfection frequency; the association between infection and different factors was established. The results showed that P. vivax was the species having the greatest frequency in the study population (61.4%), followed by P. malariae (43.8%) and P. falciparum (11.8%). The study revealed that 35.8% of the population had coinfection, the P. vivax/P. malariae combination occurring most frequently (28.3%); factors such as age, geographical origin and clinical manifestations were found to be associated with triple-infection. The prevalence reported in this study differed from previous studies in Colombia; the results suggest that diagnosis using conventional techniques could be giving rise to underestimating some Plasmodium spp. species having high circulation rates in Colombia (particularly in the Colombian Amazon region). The present study's results revealed a high prevalence of P. malariae and mixed infections in the population being studied. The results provide relevant information which should facilitate updating the epidemiological panorama and species' distribution so as to include control, prevention and follow-up measures. © 2016 Camargo-Ayala et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.